Utilization of Tofu Liquid Waste as Liquid Organic Fertilizer Using the Fermentation Method with Activator Effective Microorganisms 4 (EM-4): A Review - Lutfi Kurniawan; Maryudi Maryudi; Erna Astuti (Program studi Teknik Kimia UNS, 2024)
Liquid organic fertilizer is organic fertilizer in liquid form which is partly or wholly derived from organic compounds such as plant, animal and industrial residues, in solid or liquid form. The nutrients contained in it are in the form of a very fine solution so that it is easily absorbed by plants, even the leaves or stems. Organic fertilizer is one solution to restore soil minerals physically, chemically and biologically from the bad effects of synthetic fertilizers. Liquid fertilizer is obtained from a solid fermentation process first, then followed by a liquid anaerobic fermentation and extraction process. In the fermentation process, the role of microbes greatly determines the product produced. Tofu liquid waste is made from cooking residue from cooked soybeans boiled and the water from the remaining tofu tends to be thrown into the surrounding environment. Waste Liquid tofu contains organic ingredients, namely carbohydrates reaching 20-50%, protein 40-60%, and 10% fat. It is known that this tofu waste can be used as liquid organic fertilizer by fermentation. Tofu liquid waste contains organic substances, namely carbohydrates, proteins and fats, which can be used as liquid organic fertilizer. These substances must first be broken down into simpler elements by a fermentation process so that they can be absorbed by plants. Effective Microorganisms-4 as inoculants to increase microbial diversity in soil and can control unpleasant odors, accelerate the decomposition process, maximize the decomposition process, increase nutrient content, reduce the growth of pathogenic microorganisms, improve the physical, chemical and biological structure of the soil and bioremediation.Keywords: Liquid Organic Fertilizer, Liquid Waste, Fermentation, Effective Microorganisms-4, Nutrient